Effects of an empowerment-based intervention on health-related knowledge and resilience in patients with coronary artery stent implantation. Issue 2 (February 2021) - Wang, Mei; Hua, Yan; Liu, Xiwen; Chen, Yu; Xiao, Ting; Su, Xiangni; Shao, Pei; Ni, Chunping; Yang, Shengli
Highlights: Routine care is of limited effectiveness on knowledge and resilience improving. Patient empowerment emphasizes stimulating patients' motivation and confidence. Empowering patients with coronary heart disease greatly enhances their knowledge. Empowerment-based intervention significantly improves the level of resilience. Abstract: Objectives: To examine the effects of an empowerment-based intervention on health-related knowledge and resilience among patients after coronary artery stent implantation. Methods: This was a randomized controlled trial with a 4-week-long intervention. Participants were randomly allocated to an empowerment-based intervention group (n = 42) or control group (n = 43). Knowledge on CHD and resilience were evaluated and compared between groups. Results: Compared with the control group, patients in the intervention group showed higher score changes for CHD total knowledge ( U = 196.500; P ＜ 0.001) and its 5 dimensions including CHD definition ( U = 657.500; P = 0.022), manifestation ( U = 245.000; P ＜ 0.001), examination ( U = 639.000; P = 0.015), treatment ( U = 475.000; P ＜ 0.001), and medication ( U = 465.000; P ＜ 0.001), and higher level of resilience ( t = 3.235; P = 0.002). Conclusion: The empowerment-based intervention was effective in enhancing the knowledge on CHD and improving resilience for patients with coronary artery stent implantation. Practice implications: The structured empowerment-based intervention provides a basis for facilitating the use of this intervention in patients with coronary heart disease.